A review on nanoporous materials and its industrial applications - M.Tejaswi; M. Sudhakar; D. Prasad; I.Renukaivalya (International Journal of Pharmacy and Analytical Research, 2022)
Nanoporous materials consist of a regular organic or inorganic framework supporting a regular, porous structure. The size of the pores is generally 100 nm or smaller. Most nanoporous materials can be classified as bulk materials or membranes. Activated carbon and zeolites are two examples of bulk nanoporous materials, while cell membranes can be thought of as nanoporous membranes. A porous medium or a porous material is a material containing pores (voids). The skeletal portion of the material is often called the “matrix” or “frame.” The pores are typically filled with a fluid (liquid or gas). There are many natural nanoporous materials, but artificial materials can also be manufactured. One method of doing so is to combine polymers with different melting points, so that upon heating, one polymer degrades. A nanoporous material with consistently sized pores has the property of letting only certain substances pass through while blocking others. The applications that nanoporous materials can be used for catalysis, separation and sensing, drug delivery, etc. They are used for encapsulating drugs and allowing for a slow controlled release of the drug and many more applications that have the ability to revolutionize the way medication, sensors and catalysis due to their unique properties.